PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN SIKAP - Chariel Imelia; Musyaffa; Ika Ariyastuti Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the fact that the cooperative attitude of fourth-grade students at SDN 211/IX Mendalo Indah had not yet been optimal, as indicated by their low ability to work collaboratively in groups, take responsibility for tasks, communicate and express opinions, help one another, and actively participate during the learning process. This study aimed to improve students' cooperative attitudes through the implementation of the Jigsaw cooperative learning model and to measure the improvement in students' cooperative attitudes after the model was implemented. This study employed Classroom Action Research (CAR), which was conducted in two cycles. Each cycle consisted of the stages of planning, implementation of the action, observation, and reflection. The subjects of this study were the fourth-grade students of SDN 211/IX Mendalo Indah. The data collection techniques used were observation, interviews, and documentation. The data were analyzed using descriptive qualitative and quantitative techniques. The results showed that the implementation of the Jigsaw cooperative learning model was able to improve students' cooperative attitudes. The improvement was indicated by the increase in teacher activity from 66% in the first meeting of Cycle I to 94% in the second meeting of Cycle II, as well as student activity from 35% to 85%. In addition, students demonstrated improvements in their ability to work collaboratively, help one another, respect their classmates' opinions, take responsibility for group tasks, and actively participate in the learning process. Based on the results of the study, it can be concluded that the implementation of the Jigsaw cooperative learning model is effective in improving students' cooperative attitudes in elementary schools.